Infectious diseases prevention and control with reduced energy consumption in an airport - Tingrui Hu; Shujia Shang; Jingchao Xie; Ying Ji; Peng Xue; Nan Zhang (Energy and Built Environment)
The COVID-19 pandemic threatened the world. As an important transportation hub connecting countries and regions, airports have played a critical role in COVID-19 prevention and control. This study developed an infection risk-human comfort-energy consumption model to calculate the COVID-19 transmission and energy consumption for epidemic prevention and control in seven different functional areas of an airport during different seasons (winter, summer, and transition season) and actual passenger movement. When considering dynamic passenger flow, the energy consumption needed to prevent and control transmission of the epidemic in each area of the airport could be reduced by 71–85 %. The waiting, dining, and shopping areas were the areas with the highest energy consumption, accounting for 25–47 %, 15–32 %, and 11–38 % of the total energy consumption of epidemic prevention at the airport, respectively. The dining area had the highest energy consumption per square meter, reaching 14.2 kWh/m2 at its highest. After closing the dining area, energy consumption was reduced by 14–20 %. Compared with strict epidemic prevention and control, energy consumption in the airport was reduced by 70–85 % considering both optimized intervention and dynamic passenger flow. The results of this study provide a scientific basis for energy-saving and emission reduction in airports under an epidemic situation.